2005
DOI: 10.4049/jimmunol.175.1.293
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Dominant-Negative Fas-Associated Death Domain Protein in β Cells Protects against Fas Ligand-Induced Apoptosis and Reduces Spontaneous Diabetes in Nonobese Diabetic Mice

Abstract: In type 1 diabetes, many effector mechanisms damage the β cell, a key one being perforin/granzyme B production by CD8+ T cells. The death receptor pathway has also been implicated in β cell death, and we have therefore generated NOD mice that express a dominant-negative form of the Fas-associated death domain protein (FADD) adaptor to block death receptor signaling in β cells. Islets developed normally in these animals, indicating that FADD is not necessary for β cell development as it is for vasculogenesis. β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…The importance of the perforin pathway is probably best documented by the finding that loss of perforin greatly reduces the incidence of diabetes in NOD mice (43). Experiments with transgenic NOD mice expressing dnFADD in their ␤-cells indicated that death receptor signaling plays a partial role in diabetes development (20). Antigen-specific autoreactive cytotoxic T-cells kill ␤-cells in vitro using the Fas/FasL pathway in the absence of perforin (24,44), indicating that this mechanism may still contribute to diabetes development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of the perforin pathway is probably best documented by the finding that loss of perforin greatly reduces the incidence of diabetes in NOD mice (43). Experiments with transgenic NOD mice expressing dnFADD in their ␤-cells indicated that death receptor signaling plays a partial role in diabetes development (20). Antigen-specific autoreactive cytotoxic T-cells kill ␤-cells in vitro using the Fas/FasL pathway in the absence of perforin (24,44), indicating that this mechanism may still contribute to diabetes development.…”
Section: Discussionmentioning
confidence: 99%
“…It appears likely that these death stimuli activate other BH3-only proteins, such as Bim in the case of ER stress (41) or Puma in the case of DNA damage (42). Since ␤-cell killing induced by IFN-␥ plus IL-1␤, which requires NO production, cannot be inhibited by either loss of Bid, caspase blockade, or Bcl-2 overexpression (20), it appears likely that this death occurs through a process independent of this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated caspase-8 subsequently cleaves the effector caspase-3 and/or activates the mitochondrial death pathway via cleavage of the BH3 protein Bid. The role of Fas in T-cell mediated beta-cell destruction in vivo has remained controversial for a long time, but targeted overexpression of a dominant negative form of Fas (FADD) in beta-cells delays the onset of diabetes in NOD mice, implicating a role for Fas in the early stages of autoimmune beta-cell destruction (24,29,30).…”
Section: Mediators Of Beta-cell Destruction In T1dmentioning
confidence: 99%